Systemic Sovereign Risk: Macroeconomic Implications in the Euro Area - Saleem A. Bahaj (Oesterreichische Nationalbank (OeNB), 2014)
What are the macroeconomic implications of changes in sovereign risk premia? In this paper, I use a novel identification strategy coupled with a new dataset for the Euro Area to answer this question. I show that exogenous innovations in sovereign risk premia were an important driver of the economic dynamics of crisis-hit countries, explaining 30-50% of the forecast error of unemployment. I also shed light on the mechanisms through which this occurs. Fluctuations in sovereign risk premia explain 20-40% of the variance of private borrowing costs. Increases in sovereign risk result in substantial capital flight, external adjustment and import compression. In contrast, governments appear not to increase their primary balances in response to increases in sovereign risk. Identifying these causal effects involves isolating a source of Fluctuations in sovereign borrowing costs exogenous to the economy in question. I address this problem by relying upon the transmission of country-specific events during the crisis in Europe to the sovereign risk premia in the remainder of the union. I construct a new dataset of critical events in foreign crisis-hit countries and I measure the impact of these events on yields in the economy of interest at an intraday frequency. An aggregation of foreign events serves as a proxy variable for structural innovations to the yield to identify shocks in a proxy SVAR. I extend this methodology into a Bayesian setting to allow for flexible panel assumptions. A counterfactual analysis is used to remove the impact of foreign events from the bond yields of crisis hit countries: I find that 40-60% of the trough-to-peak moves in bond yields in crisis-hit countries are explained by foreign events, thereby suggesting that the crisis was not purely a function of weak local economic conditions.
Keywords: E44; E65; F42; 330; High frequency identi cation; Narrative identi cation; Contagion; Bayesian VARs; Proxy SVARs; Panel VARs